Cover Image, Volume 75, Issue 6. Issue 6 (18th May 2019) - Wang, Guobin; Lan, Yubin; Qi, Haixia; Chen, Pengchao; Hewitt, Andrew; Han, Yuxing
Abstract : The cover image is based on Research Article Field evaluation of an unmanned aerial vehicle (UAV) sprayer: effect of spray volume on deposition and the control of pests and disease in wheat by Guobin Wang et al., DOI:10.1002/ps.5321 . Illustration Credit: Guobin Wang, Yubin Lan, and Yuxing Han. Abstract : The cover image is based on Research Article Field evaluation of an unmanned aerial vehicle (UAV) sprayer: effect of spray volume on deposition and the control of pests and disease in wheat by Guobin Wang et al., DOI:10.1002/ps.5321 . Illustration Credit: Guobin Wang, Yubin Lan, and Yuxing Han.